Speculating the architecture of nothingness through void operations - Imanisahda, Fatiharla; Yatmo, Yandi Andri (Department of Architecture Faculty of Engineering Universitas Indonesia, 2025)
This speculative design study aims to construct the idea of nothingness as an active and generative element of architecture. Nothingness, understood as voids, empty, and negative spaces, can be reinterpreted as a productive condition that opens up new spatial possibilities. Such a productive condition demonstrates the interdependence between nothingness and the spatial existence of something. The project explores how nothingness constructs the perceptibility of particular spatial terrain through void as architectural design operations. Through creating dystopian contextual scenarios where all spaces have been used up, the study identifies various void forms present in existing structures, classifying these voids based on spatial categories and formulating the potential these voids have in shaping perception. As a result, it captures spaces that project nothingness and are lacking definition, to be transformed for spaces usable for any purpose, following the user's perception. This study suggests that architecture can originate from nothingness—to create infinite potential of new architectural proposition in the speculative contextual zones of the Neglected, the Ruin, and the Underground. Through exploring void as architectural operations, this study hopes to reflect on the expanded role of nothingness beyond simply being an overlooked, undefined aspects of space. The study concludes that the idea of nothingness may unlock various potentials in the context where space is limited but full of latent potential, such as in post-disaster or in adaptive reuse situations.